Thermoelectric properties of nanostructured porous silicon. (3rd January 2018) - Martín-Palma, R J; Cabrera, H; Martín-Adrados, B; Korte, D; Pérez-Cappe, E; Mosqueda, Y; Frutis, M A; Danguillecourt, E
Abstract: In this work we report on the thermoelectric properties of nanostructured porous silicon (nanoPS) layers grown onto silicon substrates. More specifically, nanoPS layers of different porosity, nanocrystal size, and thickness were fabricated and their electrical conductivities, Seebeck coefficients, and thermal conductivities were subsequently measured. It was found that these parameters show a strong dependence on the characteristics of the nanoPS layers and thus can be controlled.